2017
DOI: 10.1098/rsos.170431
|View full text |Cite
|
Sign up to set email alerts
|

Secondary osteons scale allometrically in mammalian humerus and femur

Abstract: Intra-cortical bone remodelling is a cell-driven process that replaces existing bone tissue with new bone tissue in the bone cortex, leaving behind histological features called secondary osteons. While the scaling of bone dimensions on a macroscopic scale is well known, less is known about how the spatial dimensions of secondary osteons vary in relation to the adult body size of the species. We measured the cross-sectional area of individual intact secondary osteons and their central Haversian canals in transv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 86 publications
(116 reference statements)
3
47
0
Order By: Relevance
“…The lack of differential cross-sectional scaling in the macropod hindlimb despite their hopping behaviour led us to the speculation that their bones might have enhanced fatigue damage repair by increased remodelling, thus reducing the need for extra bone mass. We failed to find secondary osteonal remodelling in a Macropus giganteus femur sample, which was somewhat unusual for an animal of 33kg body mass [76]. Absence of secondary osteons may relate to the single sample failing to include any by chance, a load-related suppression of remodelling protecting bone from local weakening due to osteoclastic resorption [57], or infilling of existing osteons as occurs in horses after moderate-intensity training [77].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The lack of differential cross-sectional scaling in the macropod hindlimb despite their hopping behaviour led us to the speculation that their bones might have enhanced fatigue damage repair by increased remodelling, thus reducing the need for extra bone mass. We failed to find secondary osteonal remodelling in a Macropus giganteus femur sample, which was somewhat unusual for an animal of 33kg body mass [76]. Absence of secondary osteons may relate to the single sample failing to include any by chance, a load-related suppression of remodelling protecting bone from local weakening due to osteoclastic resorption [57], or infilling of existing osteons as occurs in horses after moderate-intensity training [77].…”
Section: Discussionmentioning
confidence: 80%
“…The current and other studies of bone organ allometry assume no size-related variation in bone microstructure or physiology and that all mammalian bone has similar biomechanical and mechanobiological behavior. Our recent work demonstrated that secondary osteons are wider in larger animals and narrower in smaller animals [76], and that trabeculae are thicker and more widely spaced in larger animals [78] indicating that biophysical constraints or cellular behaviour may vary among mammals and potentially interact with whole-bone-level scaling. Integration of macro-and micro-level perspectives in future scaling studies could be particularly informative.…”
Section: Discussionmentioning
confidence: 97%
“…The lack of differential cross-sectional scaling in the macropod hindlimb despite their hopping behaviour led us to the speculation that their bones might have enhanced fatigue damage repair by increased remodelling, thus reducing the need for extra bone mass. We failed to find secondary osteonal remodelling in a Macropus giganteus femur sample, which was somewhat unusual for an animal of 33 kg body mass [ 77 ]. The absence of secondary osteons may relate to the single sample failing to include any by chance, a load-related suppression of remodelling protecting bone from local weakening due to osteoclastic resorption [ 59 ], or infilling of existing osteons as occurs in horses after moderate-intensity training [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current and other studies of bone organ allometry assume no size-related variation in bone microstructure or physiology and that all mammalian bone has similar biomechanical and mechanobiological behaviour. Our recent work demonstrated that secondary osteons are wider in larger animals and narrower in smaller animals [ 77 ], and that trabeculae are thicker and more widely spaced in larger animals [ 79 ], indicating that biophysical constraints or cellular behaviour may vary among mammals and potentially interact with whole-bone level scaling. Integration of macro- and micro-level perspectives in future scaling studies could be particularly informative.…”
Section: Discussionmentioning
confidence: 99%
“…While osteon-like structures can occasionally be observed in mice and rats, these structures lack the organization seen in larger vertebrates. A recent study has shown that osteon size positively correlates with body mass in mammals and suggested that the lack of clear osteons in small mammals may be related to the need to avoid fractures (56). Be that as it may, dysregulation of Haversian remodeling, such as may occur with aging, remains difficult to study in rodents (57).…”
Section: Genetic Manipulation Of Animalsmentioning
confidence: 99%